Cell surface damage and morphological changes in Oenococcus oeni after freeze-drying and incubation in synthetic wine - Bravo Ferrada, Barbara Mercedes (2018)
The aim of the present study was to evaluate the effects of freeze-drying in the presence of trehalose as a cryoprotectant, followed by incubation in synthetic wine, on surface damage, viability and l-malic acid consumption of the oenological strain Oenococcus oeni UNQOe 73.2. After freeze-drying, no significant differences were observed in the number of viable cells (for both acclimated and non-acclimated cultures) respect to the fresh culture. In contrast, loss of viability was observed after wine incubation for 24 h, being acclimated freeze-dried cells the best conditions for this. After the preservation process, small changes in cell morphology were observed by Atomic Force Microscopy (AFM). The Zeta potential and AFM showed that 24 h of wine incubation was enough to induce several cell surface modifications. Plate count data allowed us to establish that surface damage is an important factor for loss of viability, regardless of the acclimation treatment. Although the number of surviving O. oeni cells decreased dramatically after incubation in synthetic wine for 15 days, the consumption of l-malic acid was higher than 70%, with freeze-dried cells showing a better performance than fresh cultures. These results demonstrate that O. oeni freeze-dried cultures could be applied to direct wine inoculation, to conduct malolactic fermentation, maintaining its technological properties and reducing the time and costs of the winemaking process.